2011
DOI: 10.1186/1742-2094-8-66
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous nitric oxide decreases brain vascular inflammation, leakage and venular resistance during Plasmodium berghei ANKA infection in mice

Abstract: BackgroundCerebral malaria (CM) is a lethal complication of Plasmodium falciparum infections. In the Plasmodium berghei ANKA (PbA) murine model, CM is associated with marked brain inflammation, increased expression of endothelial cell adhesion molecules and leukocyte and platelet accumulation in brain vessels, causing vascular occlusion and decreased blood flow, damaging the endothelium and leading to blood-brain barrier breakdown, leakage and hemorrhages. Exogenous nitric oxide (NO) administration largely pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 43 publications
7
55
0
Order By: Relevance
“…Similarly to human severe malaria, low NO bioavailability has been linked to the genesis of ECM (9,22,23). We have shown that exogenous NO administration in the form of NO donors such as dipropylenetriamine NONOate (DPTA-NO) and S-nitrosoglutathione (GSNO) decreases ECM incidence, as well as cerebral edema, leukocyte accumulation, and hemorrhages (22,24,25). Similar findings were obtained with inhaled NO (26).…”
Section: Erebral Malaria (Cm) Is a Lethal Complication Ofsupporting
confidence: 53%
See 2 more Smart Citations
“…Similarly to human severe malaria, low NO bioavailability has been linked to the genesis of ECM (9,22,23). We have shown that exogenous NO administration in the form of NO donors such as dipropylenetriamine NONOate (DPTA-NO) and S-nitrosoglutathione (GSNO) decreases ECM incidence, as well as cerebral edema, leukocyte accumulation, and hemorrhages (22,24,25). Similar findings were obtained with inhaled NO (26).…”
Section: Erebral Malaria (Cm) Is a Lethal Complication Ofsupporting
confidence: 53%
“…Indeed, iNOS and eNOS upregulation has been shown to be triggered by an increase in oxidative stress under conditions of low NO bioavailability (47), similar to the conditions observed in ECM (37). Therefore, providing exogenous NO during PbA infection may prevent the very causes of iNOS and eNOS upregulation, decreasing inflammation and ameliorating endothelial function in ECM (22,24,25). Glyceryl trinitrate had a more uniform effect in preventing iNOS than eNOS upregulation, resulting in more variable expression of the latter.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The protecting effects of exogenous NO on murine cerebral malaria are associated with decreased brain vascular expression of inflammatory markers, ICAM-1 and P-selectin, resulting in attenuated endothelial damage and facilitating blood flow (Zanini et al, 2011). Previous reports demonstrated reduced NO levels in severe malaria related to impaired production of NO, reduced mononuclear cell iNOS expression and NOS substrate arginine (Anstey et al, 1996;Lopansri et al, 2003).…”
Section: Nitric Oxide-related Therapy In Hemoglobinopathiesmentioning
confidence: 99%
“…NO decreases the expression of endothelium activation markers and reduces the expression of adhesion molecules, such as ICAM-1 and P-selectin, resulting in decreased vascular permeability (61) and leukocyte and platelet adhesion (62).…”
Section: Nitric Oxidementioning
confidence: 99%